The Role of Social Studies Learning in Building Student's Social Awareness - widyawati widodo; maharani puspita dewi wardana; windi desmila; elsa nur pareza; dila septiani (Journal of Pedagogical Content Knowledge, 2025)
Social Studies (IPS) learning in primary and secondary education has a strategic role in shaping the character and social awareness of students. IPS does not only convey theoretical knowledge about social phenomena, but also functions to shape students' sensitivity, critical attitudes, and behavior in dealing with social problems that they encounter every day. By learning IPS, students are invited to understand important values, such as humanity, social justice, and responsibility towards the environment. This study uses a literature review method by utilizing data obtained entirely from various written sources, such as books, research journals, previous research reports, and other literature relevant to the research topic. The focus of this study is to understand the Role of IPS Learning in Building Students' Social Awareness. Social Studies (IPS) learning in primary and secondary education has a strategic role in shaping students' character and building high social awareness. Through an interactive, contextual, and integrative approach, IPS learning not only aims to convey theoretical knowledge, but also develops students' abilities to understand, analyze, and contribute to solving social problems around them. By linking social studies learning topics to the immediate environment, students are invited to recognize social problems around them and find relevant solutions. For example, in discussing environmental issues such as waste management or deforestation, students can be invited to conduct observations or community-based projects in their environment. Social Studies (IPS) learning has an important role in shaping students' social awareness. Through various learning materials and activities, IPS helps students understand the relationship between individuals, society, and the environment. With a relevant and contextual approach, students are invited to recognize social problems, understand diversity, and develop empathy and responsibility towards their community. This learning not only builds social insight, but also instills values of togetherness and tolerance that support the creation of a harmonious community life.